Subjective Well-Being Profile of University Students and Its Influencing Factors - Luna Nuranis Zakiah; Maya Masyita Suherman; Tb. Moh. Irma Ari Irawan; Rina Marlina; Muhammad Amirullah (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Subjective well-being is an important indicator of psychological health and life satisfaction among university students. Understanding students’ well-being is essential because academic demands, social adjustment, and developmental transitions during university life can significantly affect their psychological condition. Objective: This study aims to examine the profile of subjective well-being among university students and to identify the factors influencing it. Method: A quantitative survey design was employed, involving undergraduate students from several academic programs. Data were collected using a structured questionnaire that measured dimensions of subjective well-being, including life satisfaction, positive and negative affect, along with several potential influencing factors, such as academic stress, social support, and personal motivation. Descriptive statistics were used to describe the profile of students’ subjective well-being, while inferential analysis was applied to determine the factors associated with variations in well-being levels. Results: Students demonstrate varying levels of subjective well-being across different dimensions, with several factors showing significant relationships with overall well-being. Conclusion: These findings highlight the importance of academic and psychosocial environments in supporting students’ psychological health. Contribution: The study contributes to a better understanding of university students’ well-being. It provides educators and institutions with insights to develop strategies that enhance students’ psychological well-being and overall quality of life.